Bruce MacKenzie interviewed by Rob Willis in the Rob and Olya Willis folklore collection - MacKenzie, Bruce, 1950-; Willis, Rob, 1944-; Cameron, Bruce, 1953- (2005)
Folkloric recording.
Recorded with Bruce Cameron.
Recorded on November 23, 2005 at Nulla Nulla, N.S.W.
Digital master available
Timed summary and uncorrected transcript (typescript, 43 leaves) available.
Keywords: MacKenzie, Bruce, -- 1950- -- Interviews